Slovakia: A Catching Up Euro Area Member In and Out of the Crisis - Jarko Fidrmuc; Caroline Klein; Robert Price; Andreas Wörgötter (Institute for the Study of Labor (IZA), 2013)
The Slovak economy experienced a strong but short recession in 2009. The recovery afterwards was driven by exports and investment. While GDP growth was one of the strongest in OECD, employment did not reach the pre-crisis level and unemployment remains stubbornly high. This paper argues that Slovakia joined the euro area after a period of unprecedented real appreciation, which generated a threat for competitiveness of its export-oriented manufacturing industry. The response combined internal devaluation with productivity increasing measures, including capital deepening and laying off low productivity workers. While this strategy was successfully restoring an external equilibrium, its consequences for domestic demand and employment are less positive. This development is compared with Estonia and Slovenia, two other small and very open economies, recently entering the euro area.
Keywords: E20; F41; G01; 330; Slovak Republic; Estonia; Slovenia; crisis; job-less recovery; domestic demand; Konjunktur; Wirtschaftskrise; Eurozone; Slowakei; Estland; Slowenien